2012
DOI: 10.3109/0886022x.2011.643351
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Periodontal Diseases Reduces Chronic Systemic Inflammation in Maintenance Hemodialysis Patients

Abstract: Background: Evidences suggest that chronic systemic inflammation is associated with increasing mortality in maintenance hemodialysis patients due to atherosclerosis and malnutrition. Periodontal diseases are treatable sources of systemic inflammation in hemodialysis patients. We therefore evaluated the effect of periodontal treatment in maintenance hemodialysis patients. Method: Periodontal diseases were evaluated in 30 stable maintenance hemodialysis patients by using clinical periodontal status by plaque ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 48 publications
6
44
1
1
Order By: Relevance
“…These authors related their obtained results to the relatively small number of patients. The findings of their study were consistent with those of Idle et al 43 Siribamrungwong et al 39 found significant decrease in the serum levels of CRP 8 weeks after the completion of periodontal treatment in 30 maintenance hemodialysis patients. Vilela et al 37 also reported the reduction of CRP, IL-6, and prohepcidin levels in both CKD and control patients 12 weeks following periodontal treatment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These authors related their obtained results to the relatively small number of patients. The findings of their study were consistent with those of Idle et al 43 Siribamrungwong et al 39 found significant decrease in the serum levels of CRP 8 weeks after the completion of periodontal treatment in 30 maintenance hemodialysis patients. Vilela et al 37 also reported the reduction of CRP, IL-6, and prohepcidin levels in both CKD and control patients 12 weeks following periodontal treatment.…”
Section: Discussionsupporting
confidence: 87%
“…37 There are different studies that reveal the association between high serum levels of CRP and the severity of periodontitis in ESRD who are on hemodialysis. 7,38,39 Although there are numerous studies that have examined the effect of different periodontal treatment modalities on serum CRP levels in chronic periodontitis patients, this is scarcely performed on patients suffering from both periodontitis and CKD. From the first category, many treatment studies show an effect on CRP levels in favor of periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory serum biomarkers associated with the risk of coronary heart disease in prospective studies Acute-phase reactants High-sensitive C-reactive protein (Ridker et al 1998) Lipoprotein-associated phospholipase A2 (Madjid et al 2010 (Hwang et al 1997) sE-selectin (Hwang et al 1997) Vascular endothelial growth factor Placental growth factor (Lenderink et al 2006) White blood cell counts (Madjid et al 2004) periodontal therapy on WBC (Appendix S4). Christgau et al (1998) failed to show any differences in WBC in patients with diabetes and healthy controls 4 months after periodontal treatment; these findings were confirmed in other trials (Montebugnoli et al 2005, Seinost et al 2005, Marcaccini et al 2009a, Graziani et al 2010, Siribamrungwong & Puangpanngam 2012 (Rastogi et al 2012). That efficacy was further confirmed in three additional clinical trials (Fokkema et al 2003, Hussain Bokhari et al 2009, Piconi et al 2009).…”
Section: Inflammatory Markerssupporting
confidence: 73%
“…The recent years have witnessed an emerging evidence which has linked periodontitis to various systemic illnesses and it was confirmed that the periodontal health was poor in haemodialysis patients and that it correlated with the markers of malnutrition and inflammation [21]. The treatment of periodontal diseases reduces the chronic systemic inflammation in maintenance haemodialysis patients [22] by inducing a decline in the systemic inflammatory response [23]. Further studies could evaluate whether the treatment of periodontitis would translate into the amelioration of an inflammatory and protein depletion state and they could confirm a cause-effect relationship which leads to improved outcomes in the haemodialysis population.…”
Section: Resultsmentioning
confidence: 99%